Neutrophil to lymphocyte ratio predicts pattern of recurrence in patients undergoing liver resection for colorectal liver metastasis and thus the overall survival. Issue 4 (29th December 2014) - Giakoustidis, Alexandros; Neofytou, Kyriakos; Khan, Aamir Z.; Mudan, Satvinder
<x xml:space="preserve">Abstract</x> Objective We investigate the neutrophil to lymphocyte ratio (NLR) as a potential prognostic factor for patients undergoing curative liver resection for colorectal liver metastasis (CRLM). Methods We identified patients who underwent liver resection, via our prospectively accumulated surgical database at the Royal Marsden Hospital and The London Clinic, by two liver surgeons (SM and AZK) between January 2005 and December 2012 and patients included had liver resection for CRLM and received preoperative chemotherapy with an NLR > 2.5 considered elevated. NLR's role in disease‐free, post‐recurrence and overall survival was determined by univariate and multivariate Cox regression models. Results One hundred and sixty nine patients were enrolled. Seventy‐one patients (42%) demonstrated NLR > 2.5. Elevated NLR was associated with decreased OS in univariate and multivariate analysis (HR 2.12; 95% CI, 1.18–3.82; P = 0.012) but not with DFS. Analyzed as continuous variable, higher NLR was associated with decreased OS(HR 1.17; 95% CI, 1.03–132; P = 0.011) and associated with increased risk of extrahepatic/multifocal recurrence (P = 0.007), linked in this way with a decreased post‐recurrence survival (HR 1.24, 95% CI, 1.02–1.52; P = 0.032). Conclusions Elevated NLR in patients who undergo hepatectomy following neoadjuvant chemotherapy for CRLM increases risk of extrahepatic/multifocal recurrence and is an independent predictor of overall survival. J. Surg. Oncol. 2015 111:445–450. © 2014 Wiley Periodicals, Inc.